Pelaksanaan Hak Kunjungan Keluarga Terhadap Warga Binaan di Lembaga Pemasyarakatan Kelas IIB Singaraja - Jones Peringa Sembiring; Si Ngurah Ardhya; I Komang Wiranata (Universitas Pendidikan Ganesha, 2026)
Visitation rights are one of the rights possessed by Correctional Inmates as a form of fulfillment of human rights and as a means to maintain social relations with family and society during the period of serving a sentence. The implementation of visitation rights in correctional institutions exerts a vital function in bolstering the mentoring procedure, but realistically, a variety of barriers persist, which may impact the optimal execution of its implementation. The purpose of this research is to analyze how the execution of Correctional Inmates' visitation rights is carried out pursuant to Law Number 22 of 2022 concerning Corrections and to discern the elements that affect this operation at the Class IIB Singaraja Correctional Institution. The present paper uses a realistic juridical methodology featuring a sociological law perspective. Data were obtained via personal dialogues, fieldwork observations, and document analyses, then examined qualitatively in a narrative manner. The findings demonstrate that the way the implementation of visitation rights is managed within Singaraja Class IIB Correctional Institution has basically referred to the applicable laws and regulations through registration mechanisms, identity verification, security checks, and supervision during visits. Nonetheless, its execution is currently confronting a number of impediments, encompassing limited facilities and infrastructure, overcrowded inmate conditions, and a limited number of correctional officers. Therefore, it is necessary to optimize visitation service facilities, improve the quality of supervision, and strengthen human resources in order to guarantee that the privilege of visitation rights of Correctional Inmates is fulfilled effectively as well as in accordance with correctional tenets.